2012
DOI: 10.1039/c1dt11729g
|View full text |Cite
|
Sign up to set email alerts
|

A novel structural form of MIL-53 observed for the scandium analogue and its response to temperature variation and CO2adsorption

Abstract: The scandium analogue of the flexible terephthalate MIL-53 yields a novel closed pore structure upon removal of guest molecules which has unusual thermal behaviour and stepwise opening during CO(2) adsorption. By contrast, the nitro-functionalised MIL-53(Sc) cannot fully close and the structure possesses permanent porosity for CO(2).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
114
1

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(118 citation statements)
references
References 25 publications
3
114
1
Order By: Relevance
“…As a result, the crystal building of this compound can be described as a dense 3D Cd-pmdc framework, that possesses the (4 4 . 6 6 ) point symbol, which is a subnet of the topological sev net ( Figure 5).…”
Section: Crystal Structure Of [Cd(μ 5 -Pmdc)] N (3)mentioning
confidence: 99%
“…As a result, the crystal building of this compound can be described as a dense 3D Cd-pmdc framework, that possesses the (4 4 . 6 6 ) point symbol, which is a subnet of the topological sev net ( Figure 5).…”
Section: Crystal Structure Of [Cd(μ 5 -Pmdc)] N (3)mentioning
confidence: 99%
“…This phenomenon has been reported for several soft PCP motifs, e.g., one-dimensional channels, 5 two-dimensional stacked layers, [6][7][8][9][10][11] and threedimensional interpenetrating motifs. [12][13][14] The breathing phenomenon, which is typically observed for MIL-53 family, [15][16][17][18][19][20] consists of abrupt shrinkage of the host structure followed by expansion upon adsorption. The soft PCPs have shown different structural transition behaviors, which could be suitable for various applications such as gas storage, 7, 21 separation, 9 and molecular sensing; 22 however, for their application in industry, precise control of the structural transition behavior is required.…”
Section: Introductionmentioning
confidence: 99%
“…104 The Sc-based form of MIL-53 also exhibits a series of phase transitions, which can be followed using NMR spectroscopythe effect of hydration upon the 45 Sc NMR spectrum was shown previously in Figure 2(c). 34 The utility of MIL-53 MOFs for drug delivery has also been recently demonstrated. C chemical shifts of the loaded drug confirmed that it adopted a conformation close to that of its pure form -a conclusion that was also supported by complementary DFT calculations.…”
Section: Page 28 Of 60 Physical Chemistry Chemical Physicsmentioning
confidence: 99%
“…The resolution advantage of MQMAS is clear in Figure 2(c), where 45 Sc NMR spectra of two forms of MIL-53(Sc) are shown. 34 Although the MAS spectra look fairly similar (each containing broad has inherently higher sensitivity than MQMAS, it is significantly more challenging to implement, requiring a very accurate setting (to 54.736° ± 0.002°) of the spinning axis, accurate pulse timings and very stable sample spinning. 45 This has generally limited its application in comparison to MQMAS, although it has been applied to phosphate-based frameworks.…”
Section: Basic Approaches To Nmr Of Microporous Materialsmentioning
confidence: 99%